Formulasi dan Evaluasi Sediaan Nanoemulsi Ekstrak Umbi Bawang Putih (Allium sativum L.): Formulation and Evaluation of Nanoemulsion of Garlic (Allium sativum L.) Extract - Alvira Intan Widyastuti; Dwi Saryanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Garlic bulbs (Allium sativum L.) has an active substance in the form of allicin which is thermolabil, allicin as the main antioxidant that can prevent free radicals. Nanoemulsion has a particle size of 20-500 nm which is an oil and water dispersion system stabilized by a combination of surfactant and cosurfactant. The purpose of this study was to obtain the best formula from the variation of VCO concentration 3%, 5%, 8% and determine the stability of nanoemulsion preparations. Nanoemulsions are formulated in oil phase VCO, surfactant Tween 80, and cosurfactant PEG 400. Nanoemulsion preparation performed organoleptic test, pH, viscosity , transmittance%, stability. The best Formula continued particle size test, and zeta potential. This study used laboratory experimental method, the results of the study were analyzed by one way ANOVA test. Obtained the best formula of nanoemulsion preparation of garlic bulb extract at a concentration of 8% VCO, the best formula physical results with clear yellow organoleptic characteristics, distinctive odor, and does not separate, pH value 4.9, viscosity value 7.0 d'pas, transmitan % value 96.11, nanoemulsion preparation of garlic bulb stable after stability test. The best Formula in Continue particle size test is the average value obtained 607.0, 53.4 and the average value of the potential Zeta test obtained -5.7, 0.86. The higher the concentration of VCO, the stability of smakin good preparation, nanoemulsion preparation that has good stability in formula 3 with a concentration of 8% VCO. Keywords: Nanoemulsion, Antioxidants, VCO, PEG 400, Tween 80 Abstrak Umbi bawang putih (Allium sativum L.) memiliki zat aktif berupa allicin yang bersifat termolabil, allicin sebagai antioksidan utama yang dapat mencegah radikal bebas. Nanoemulsi memiliki ukuran partikel 20-500 nm yang merupakan suatu sistem dispersi minyak dan air yang distabilkan oleh kombinasi surfaktan dan kosurfaktan. Tujuan penelitian ini untuk mendapatkan formula terbaik dari variasi konsentrasi VCO 3%, 5%, 8% dan mengetahui kestabilan sediaan nanoemulsi. Nanoemulsi diformulasikan dalam fase minyak VCO, surfaktan Tween 80, dan kosurfaktan PEG 400. Sediaan nanoemulsi dilakukan uji organoleptis, pH, viskositas, % transmitan, stabilitas. Formula terbaik dilanjutkan uji ukuran partikel, dan zeta potensial. Hasil penelitian dianalisis dengan uji one way anova. Berdasarkan % transmitan tertinggi didapatkan formula terbaik sediaan nanoemulsi ekstrak umbi bawang putih pada konsentrasi VCO 8%, dengan karakteristik organoleptis kuning bening, bau khas, dan tidak memisah, pH 4,9, viskositas 7,0 d’Pas, % transmitan 96,11%. Sediaan nanoemulsi umbi bawang putih stabil setelah dilakukan uji stabilitas. Formula terbaik mempunyai ukuran partikel yaitu 607,0±53,4 nm dan nilai zeta potensial sebesar -5,7±0,86 mV. Semakin tinggi konsentrasi VCO maka stabilitas sediaan semakin baik, sediaan nanoemulsi yang memiliki stabilitas yang baik yaitu pada formula 3 dengan konsentrasi VCO 8%. Kata Kunci: Nanoemulsi, Antioksidan, VCO, PEG 400, Tween 80